Technical and economic efficiency analysis of the Portuguese artisanal dredge fleet - Manuela M. Oliveira (2010)
An efficiency analysis of the commercial dredge fleet operating along the south coast of Portugal between 2005 and 2007 sought todetermine the efficiency of the vessels using data envelopment analysis models, considering fixed inputs (vessel power, length, tonnage,and an indicator of stock biomass) and a variable input (number of days at sea). The annual quota per vessel was also included in themodel as a contextual factor. In the technical-efficiency (TE) analysis, outputs were defined by the catch weight for each of the threetarget species (bivalves). Using price data for each species in the wholesale market, revenue efficiency was also estimated to complementthe TE analysis. The advantage of the approach lies in the ability to separate technical aspects from allocative aspects inthe efficiency assessment, allowing two-dimensional graphic representation of vessel performance. The procedure allows the identifi-cation of benchmark vessels, which maximized the catch weight of the species landed, given their inputs, as well as the vessels thatselected the appropriate target species to maximize the revenue of the fishing activity, given output prices. The approach also allowedthe specification of targets for inefficient vessels that correspond to the catch by species, permitting revenue maximization fromfishing.